Two new species of Tingidae (Hemiptera: Heteroptera) from Panama - Knudson, Alexander H.; Rider, David A.; Knodel, Janet J. (Zootaxa, 2021)
Two new species of Tingidae are described from Panama: Acanthotingis deltoides sp. nov. and Stephanitis joceliae sp. nov. Descriptions and diagnosis for both Acanthotingis Monte and Stephanitis Stål are provided, and a key is given for the separation of the two known species of Acanthotingis. This is the first record of both genera from Panama. A checklist of all Neotropical species of both genera is presented.